Acceptance of vaccination against pertussis, COVID-19 and influenza during pregnancy: a cross-sectional study - Veja Widdershoven; Rianne P. Reijs; Annika Eskes; Amanja Verhaegh-Haasnoot; Christian J.P.A. Hoebe (BMC, 2023)
Abstract Background This study aims to assess the uptake of maternal pertussis and COVID-19 vaccination and the intention towards accepting the maternal influenza vaccination. Insights into different socio-demographic factors related to maternal vaccination coverage might help to address vaccine acceptance and improve maternal vaccine uptake in the future. Methods We conducted a cross-sectional survey among pregnant women and recent mothers, up to 6 months post-partum. The primary outcome measures of this study were behaviour for maternal pertussis and COVID-19 vaccination, and maternal influenza vaccination intention. Associations between socio-demographic factors and maternal pertussis vaccination and maternal COVID-19 vaccination behaviour; and socio-demographic factors and maternal influenza vaccination intention were assessed using binary logistic regression analyses. Results In total 1361 respondents filled out the questionnaire. Almost all women (95%) were vaccinated against pertussis during pregnancy, while almost two-third were vaccinated against COVID-19 during pregnancy (58%) and almost one-third (28%) had a positive intention towards receiving the maternal influenza vaccination. Results show that young maternal age and low education level were associated with lower maternal vaccination acceptance. Conclusion Vaccination campaigns focusing on the severity of diseases that are prevented, are needed to increase maternal vaccine acceptance in younger and low-educated pregnant women. We expect that differences in vaccination coverage between the three maternal vaccinations might partly be explained by existing recommendations, campaigns and whether the vaccination is part of the national immunisation program.